Aplikasi Monitoring Tahfidz “SI Huffadz” Berbasis Web Studi Kasus MI Mathla’ul Anwar Twelagiri - Shintya Wahyu Ramadhan; Muh. Zia Ulkhaq; Tutut Dwi Prihatin (CV. ITTC INDONESIA, 2025)
MI Mathla'ul Anwar Twelagiri is one of the Islamic educational institutions that has a tahfidzul qur'an program. One important factor that can influence the process of memorizing students is the monitoring system. MI Mathla'ul Anwar Twelagiri uses a liaison book as a medium for monitoring student memorization. However, based on research from interviews, observations, and documentation, the monitoring process is still less effective because parental involvement in monitoring memorization at home is relatively low, communication between teachers and parents tends to be one-way, and lost or damaged liaison books make the evaluation of student development inconsistent. In this study, a Web-Based tahfidz monitoring application 'SI Huffadz' was created using the CodeIgniter 4.0 framework and the waterfall development method to solve the above problems by testing the quota sampling system taken from 20 respondents and obtained the results of the scores from admin respondents 84%, teachers 85%, and guardians 81.6%. From the results of the questionnaire, the tahfidz monitoring application 'SI Huffadz' that was created can be used by madrasas, especially teachers supervising the tahfidzul Qur'an program to increase the effectiveness in the process of monitoring the development of student memorization.